Upaya Meningkatkan Motivasi Belajar Seni Rupa melalui Media Pameran Karya Seni Siswa Kelas VII.B SMP Negeri 12 Mataram - Ariani, Komang (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine the increase in motivation to learn Cultural Arts through an exhibition of Artwork by Class VII.B students of SMP Negeri 12 Mataram in the Academic Year 2021/2022. The form of this research is classroom action research using a cycle model. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The number of students in class VII.B SMP Negeri 12 Mataram. Learning Cultural Arts by using art exhibition media can increase student learning motivation. This can be seen from the increase in student learning outcomes in each cycle. The results of observations on teacher activities experienced an increase in learning planning from cycle I of 60.00%, to 70.00% cycle II and to 80.00% cycle III. Implementation of learning increased in cycle I by 66.67%, to 75.00% in cycle II and to 83.34% in cycle III. While student activity between cycle I became 60.71%, became 71.43% cycle II and became 89.29% cycle III. Based on the initial test the number of students who had not completed 15 students or 44.12% and students who completed 19 students or 55.88%, after the implementation of cycle I was reduced to 12 students or 35.29%, students who completed 22 students or 64.71 %, to 6 students or 17.65% in cycle II students who completed 28 students or 82.35%, and to 2 students or 5.88 in cycle III. students who completed 32 students or 94.12%. Thus the implementation of art exhibition media for class VII.B students of SMP Negeri 12 Mataram received very positive responses or responses from students so that their use could be stated to be very good.